2018
DOI: 10.3390/environments5080088
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aluminium Salt Dosing for Chemical Phosphorus Removal on the Settleability of Activated Sludge

Abstract: The use of metal salts like aluminium in the precipitation of phosphorus in activated sludge plants has increased considerably in recent years due to the need to achieve tighter discharge consents for phosphorus in treated wastewater effluent. The impact of aluminium salt (Al3+) dosing on the settleability of activated sludge as a function of zone settling velocity (ZSV) and stirred specific volume index (SSVI) were investigated in batch settleability tests over a three-year period. The results showed that ZSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In an earlier study by Ojo and Ifelebuegu [19], the batch settling test measurements of zone settling curve (ZSC) of ZSV reveals ZSV as a linear representation ( Figure 1) of sludge height as a function of time (m/h) for 100 mg/L Al 3+ dosed sludge. Also, the results as previously reported [19] showed that the ZSV increased, while SSVI decreased with increasing concentrations of Al 3+ salt up to <100 mg/L. Beyond this concentration the sludge settleability disintegrated due mainly to surface charge reversal.…”
Section: Model Development and Model Validity For Al 3+ Dosed Sludgementioning
confidence: 86%
See 4 more Smart Citations
“…In an earlier study by Ojo and Ifelebuegu [19], the batch settling test measurements of zone settling curve (ZSC) of ZSV reveals ZSV as a linear representation ( Figure 1) of sludge height as a function of time (m/h) for 100 mg/L Al 3+ dosed sludge. Also, the results as previously reported [19] showed that the ZSV increased, while SSVI decreased with increasing concentrations of Al 3+ salt up to <100 mg/L. Beyond this concentration the sludge settleability disintegrated due mainly to surface charge reversal.…”
Section: Model Development and Model Validity For Al 3+ Dosed Sludgementioning
confidence: 86%
“…The mixed liquor samples (MLSS concentration of the samples ranged from 2800 to 3500 mg/L, with the pH ranging from 6.5 to 7.5 and a phosphate concentration of 7 to 12 mg/L) were sampled in 32.5 L sample containers from the distribution chambers and analysed in the laboratory within 24 h of sampling. Details of the methods have been previously described [19].…”
Section: Sludge Sampling and Analysismentioning
confidence: 99%
See 3 more Smart Citations